APPLICATION RESEARCH OF REMESHING TECHNIQUE ON RUBBER NUMERICAL SIMULATION - LV FengXia; ZHOU Li; YUAN HuiXin; ZHANG Yan; YANG He (Jixie qiangdu)
For the large deformation and distortion of the mesh on the numerical simulation of rubber,using the solving and transformation between grids of the adaptive technique of Abaqus software,the rubber model was remeshed several times. In this paper,the key parts of the packer were used as the research object and the final rubber deformation results were obtained by two remeshing before solving the mapping to the new mesh for further solving. The results of numerical simulation show that remeshing can reduce the occurrence of distortion and solve the problem of nonlinear analysis of large deformation caused by mesh distortion.Remeshing can improve the accuracy of data transmission between the old and new grid when the old mesh has a smaller distortion. It provides a significant research method for the sealing performance of the rubber,which also has some reference value for other hyperelastic materials.